Hubungan antara Dukungan Sosial Keluarga dan Tingkat Stres Psikologis pada Remaja Tunanetra - Hidayat, Novi; Ikromi, Ziyadi Ali (Universitas Lancang Kuning, 2025)
This research aimed to gain an in-depth understanding of the relationship between family social support and psychological stress levels among visually impaired adolescents residing in Bekasi, Indonesia. Utilizing a quantitative approach with a correlational design, the study involved 105 visually impaired adolescents aged 12 to 18 years as participants. Data collection was carried out using two primary instruments: the Family Social Support Scale (a modified version of the MSPSS) to measure perceived support, and the Adolescent Psychological Stress Scale (a modified version of the PSS) to assess experienced stress levels. The analysis results showed a significant and strong finding: there was a strong and significant negative correlation between perceived family social support and psychological stress levels in visually impaired adolescents. This was evidenced by a correlation coefficient of r=−0.68 and a very low probability value of p<0.001. This figure indicates that the higher the support adolescents received from their families, the lower their psychological stress levels were. These findings reaffirm the crucial role of family as a vital protective and buffering factor for the mental health and psychological well-being of visually impaired adolescents. Therefore, this research recommends developing and strengthening family-based interventions as an effective effort to enhance the psychological well-being of this adolescent group.